Using mobile phone data for epidemic response in low resource settings—A case study of COVID-19 in Malawi. (9th August 2021) - Green, Dylan; Moszczynski, Michael; Asbah, Samer; Morgan, Cassie; Klyn, Brandon; Foutry, Guillaume; Ndira, Simon; Selman, Noah; Monawe, Maganizo; Likaka, Andrew; Sibande, Rachel; Smith, Tyler
Abstract: The COVID-19 global pandemic has had considerable health impact, including sub-Saharan Africa. In Malawi, a resource-limited setting in Africa, gaining access to data to inform the COVID-19 response is challenging. Information on adherence to physical distancing guidelines and reducing contacts are nonexistent, but critical to understanding and communicating risk, as well as allocating scarce resources. We present a case study which leverages aggregated call detail records into a daily data pipeline which summarize population density and mobility in an easy-to-use dashboard for public health officials and emergency operations. From March to April 2021, we have aggregated 6-billion calls and text messages and continue to process 12 million more daily. These data are summarized into reports which describe, quantify, and locate mass gatherings and travel between subdistricts. These reports are accessible via web dashboards for policymakers within the Ministry of Health and Emergency Operations Center to inform COVID-19 response efforts and resource allocation.